Quantum computing applied to reconfigurable hardware with a focus on information security - Fernandes, Gustavo Inácio Arraes; Filgueiras, Gabriel Tauchen; Gomes, Otávio de Souza Martins (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on CybersecurityDO - 10.5753/sbseg_estendido.2025.13963, 2025)
This work presents the implementation of a quantum circuit emulator on FPGA, focusing on the application of Grover’s search algorithm. The system transmits the amplitude coefficients of quantum states via UART to a microcontroller, enabling practical validation through comparison with simulations performed in Qiskit. The architecture, based on fixed-point arithmetic, achieved results consistent with theoretical models while requiring minimal logical resources. The relevance of Grover’s algorithm to post-quantum cybersecurity is discussed, as well as the potential of the proposed prototype as a tool to support the analysis and mitigation of cryptographic vulnerabilities.